OPN Deficiency Increases the Severity of Osteoarthritis Associated with Aberrant Chondrocyte Senescence and Apoptosis and Upregulates the Expression of Osteoarthritis-Associated Genes. (22nd October 2020) - Tian, Jian; Cheng, Chao; Kuang, Shi-Da; Su, Chao; Zhao, Xin; Xiong, Yi-lin; Li, Yu-Sheng; Gao, Shu-Guang
Abstract : Objectives . A recent work has reported that the elevated osteopontin (OPN) levels in the articular cartilage and synovial fluid are correlated with the progressive osteoarthritis (OA) joint damage, and OPN has a protective effect against OA by suppressing the expressions of OA-associated genes. The present study examined whether the OPN deficiency was susceptible to OA through the regulation of chondrocyte senescence and apoptosis and the expressions of OA-associated genes. Methods . The mRNA levels of COL2A1 and OPN were compared between human OA chondrocytes and normal chondrocytes. The effects of OPN siRNA on the SA- β -Gal expressions and the percentage of apoptotic chondrocytes were examined by using SA- β -Gal staining and apoptosis assay, and the effects on the expressions of COL2A1 and OA-associated genes (COL10A1, IL-1 β, TNF-ɑ, MMP-13, and ADAMTS5) were examined by western blot analysis and quantitative real-time RT-PCR. Furthermore, an in vivo OA model was established to examine the effects of OPN siRNA on the senescence and apoptosis of OA chondrocytes and the expressions of OA-associated genes. Results . The mRNA levels of COL2A1 and OPN were decreased in knee OA chondrocytes in comparison with those in normal chondrocytes. The OPN deficiency enhanced the senescence and apoptosis of OA chondrocytes and increased the expressions of COL10A1, IL-1 β, TNF-ɑ, MMP-13, and ADAMTS5 but decreased the expression of COL2A1. Meanwhile, OPN deficiency could result in severe, accelerated OA in vivo, which was also associated with enhanced senescence and apoptosis of chondrocytes and elevated expressions of OA-associated genes. Conclusions . The findings of this study suggest that the OPN deficiency can result in accelerated OA, which is associated with enhanced senescence and apoptosis of OA chondrocytes and the upregulated expressions of OA-associated genes.